Will Greece go Bankrupt and kill the euro? - Grubel, Herbert Grubel (REVISTA PROCESOS DE MERCADO, 2013)
This paper compares the benefits to Greece, the Euro zone and the rest of the world arising from policies that prevent a Greek default and exit from the Euro with the costs of preventive policies. It concludes that the benefits exceed the costs, though unpredictable politics and nationalist aspirations may prevent the adoption of the rational policies. The paper also considers the causes of Greece’s problems: the failure of lenders to ask for a proper risk premium on the country’s bonds; Greece’s publication of false economic data; the failure of credit rating agencies to down-grade its bonds; the global financial euphoria and supply of liquidity that made lenders disregard traditional standards in all their dealings. The paper recommends policies to ensure the proper functioning of financial markets to prevent future crises. Key words: Greece bankruptcy, Euro survival, Greek statistics, Credit ratings. JEL Classification: F33, F34, F36, F55, G15, G24. Resumen: Este artículo compara los beneficios con los costes derivados del salvamento griego, llegando a la conclusión de que los beneficios superan claramente a los costes. También se analizan las causas del problema, el papel de las sociedades de rating y la euforia previa especulativa, efectuán-dose unas consideraciones sobre el futuro del euro y del orden financiero internacional. Palabras clave: Bancarrota Griega, Euro, Estadísticas en Grecia, Credit ratings. Clasificación JEL: F33, F34, F36, F55, G15, G24.